A Video On Demand System Architecture For Heterogeneous Mobile Ad Hoc Networks For Different Devices. - K.Alomari, Saleh Ali; Sumari, putra (2010)
this paper proposed new system architecture for Mobile Ad Hoc Networks (MANETs) on heterogeneous network to provide optimal Video on Demand (VoD) services to difference types of devices with optimal bandwidth utilization.